The Impact of Teacher Professional Development Programs Incorporating Educational Technology on Student Achievement: A Meta-Analysis - Samsudin (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
The objective of this study is to ascertain the role and influence of technology in the field of education. This research employs a qualitative research method utilizing library research methodologies. Technology in education is an integrated system that facilitates instructional processes to achieve optimal results. There is a persistent discrepancy between the advancements in both education and technology and the broader progression of humanity. In this endeavor, educational technology necessitates the integration of diverse components, including tools and mechanisms for information collection, analysis, and problem resolution. The advantages encompass the addition of knowledge, augmented learning capacity, and the simplification of this technology's learning processes.